Specialization in Neuroscience. Current status of the problem and suggestions for resolving - Jerí, Raúl (1964)
Neuropathology, neurosurgery and neurology: After briefly reviewing the current trends in the training of specialists, the essential requirements to become an institution to start a medical residency program, especially in relation to the three fundamental neurological disciplines are described. Then the characteristics of the currently teaching hospitals affiliated with the Faculty of Medicine of the University of San Marcos are discussed, pointing out the deficiencies is urgent to repay, and the changes in organization and equipment to be set before opening the residency program. Finally, a project is presented for neurological residences, using the personnel, facilities and equipment currently available in the Dos de Mayo, Loayza, Child, Santo Toribio and Larco Herrera hospitals.